Myofascial Pain Syndrome Of The Upper Trapezius Muscle: Different Effects Of Myofascial Release And Stretching On Pain - Nitaya Putri Nur Hidayati; Aji Puspa Wardana (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Background: The increasing demand of works from day to day and unergonomic posture habits and static positions at works for a longer period of time can cause physical symptoms such as muscle spasm and pain especially on the neck area or known as myofascial pain upper trapezius muscle. The pain can limit daily functional activities so that invidivual with this problem usually seek for treatment to reduce it. Physiotherapy intervention that can be used in this case among others are myofascial release and stretching. Objective: To know the difference between the effect of myofascial release with stretching on myofascial pain upper trapezius muscle. Research Methods and Result: This research is an experimental study with two group with pre and post test design. The sampling technique was purposive sampling. The subject is 30 workers in Fitasoma Clinic who fulfill inclusion criteria and divided into two groups namely group I (n=15) with myofascial release treatment and group II (n=15) with stretching. Each group received treatment 6 times for 2 weeks. The assessment of pain in this research used quadruple visual analogue scale (QVAS). During pre and post-test group I and II used paired t test and each group got the score of p=0,000. Meanwhile, in post-test group I and II used unpaired t test and got the score of p=0,009. Conclusion: This research shows that myofascial release and stretching is effective to reduce pain on myofascial pain upper trapezius muscle. However, myofascial release is more effective than stretching to decrease pain on myofascial pain upper trapezius muscle.